N-ACYL HOMOSERINE LACTONASE SECRETION FROM BACILLUS LICHENIFORMIS DAHB1 IN THE PERIPLASMIC AND EXTRACELLULAR REGIONS OF ESCHERICHIA COLI BL21 (DE3) - Nurwinda Destari, Dianti
Quorum sensing (QS) can activate gene expression systems in pathogenic bacteria such as Vibrio sp. to produce the main virulence factors that cause Acute Hepatopancreatic Necrosis Disease (AHPND). AHPND can exacerbate vibriosis and cause death, thereby reducing shrimp productivity. This QS mechanism can occur through the accumulation of chemical signaling molecules, such as N-acyl homoserine lactones (AHLs). The quorum quenching (QQ) approach can be used to inhibit QS by reducing the accumulation of AHLs using N-acyl homoserine lactonase. N-acyl homoserine lactonase is one of the most studied QQ enzymes because it can hydrolyze cyclic homoserine lactone rings in various AHLs with different molecular chain lengths. N-acyl homoserine lactonase is found in many bacterial species, especially in the Bacillus genus, such as Bacillus licheniformis DAHB1. N-Acyl homoserine lactonase from B. licheniformis DAHB1 was expressed in Escherichia coli. This enzyme has high activity, specificity for a wide range of substrates, wide temperature and pH profiles, and is resistant to acidic conditions in the shrimp gut and various proteases. However, most of these enzymes tend to form insoluble aggregates (inclusion bodies) within the cytoplasm of E. coli. The formation of inclusion bodies can reduce bioactivity and complicate the downstream processing of recombinant proteins. One of the innovations that can be carried out to minimize downstream processes is the secretion of N-acyl homoserine lactonase from the cytoplasm into the periplasm and extracellular cells of E. coli BL21 (DE3). The secretion of N-acyl homoserine lactonase into the periplasm and extracellular cells of E. coli BL21 (DE3) can be achieved by genetic engineering. Genetic engineering involved adding the PelB signal peptide contained in the pET-26b(+) expression vector and the 20 amino acid N-terminal (N20) of the cellulase catalytic domain of Bacillus sp. Z-16 at the start of the recombinant protein. Therefore, this study aimed to express N-acyl homoserine lactonase from B. licheniformis DAHB1 and secrete it into the periplasm and extracellular parts of E. coli BL21 (DE3) using the recombinant plasmids pET-26b(+)-aiiA-6xHis and pET- 26b(+)-N20-aiiA-6xHis. v This study was conducted in several stages, including bioinformatics studies and synthesis of N-acyl homoserine lactonase, transformation of recombinant plasmids in E. coli BL21 (DE3), recombinant protein secretion at 25°C with various incubation times after induction with 0.5 mM IPTG ( 16, 20, and 38 h), and IPTG concentrations (0, 0.5, 0.75, and 1 mM). Isolation of recombinant proteins from the periplasm and extracellular tissue was performed using the osmotic shock method and a protein concentrator, respectively. The secretion of recombinant protein bands on SDS-PAGE gels was analyzed using the ImageJ software. Recombinant protein purification was performed using Ni-NTA spin columns. Dialysis of recombinant protein was performed using a dialysis tube. Enzyme activity was calculated based on the decrease in substrate, as measured by UPLC-ESI-MRM/MS. The results of bioinformatics studies predict that the N-acyl homoserine lactonase from B. licheniformis DAHB1 has different amino acid residues at positions 73 and 138, which are thought to characterize substrate specificity. The addition of N20 to the target protein causes negatively charged polar amino acids to concentrate at the N-terminus, so that the N-terminus of the target protein is a hyperexporter. The mature proteins aiiA-6xHis (29.14 kDa) and N20-aiiA-6xHis (31.61 kDa) are predicted to be soluble and can be secreted into the periplasm and extracellular cells of E. coli BL21 (DE3). The addition of N20 and His-Tag to the target protein was predicted to cause differences in the tertiary structures of the N-terminus and C-terminus. DNA sequencing confirmed the absence of mutations in the nucleotide sequences of the two target genes. The results of recombinant protein secretion showed that the highest percentage of aiiA-6xHis ratio (p <0.05) of 11.58% was observed in the periplasm under growth conditions of 25°C and 20 h of incubation after induction with 0.75 mM IPTG. The highest percentage of N20-aiiA-6xHis ratio (p <0.05) of 14.58% was secreted in the periplasm under the same growth conditions as 0.5 mM IPTG induction. The highest percentage ratios of aiiA-6xHis (p <0.05) and N20-aiiA-6xHis (p <0.05) were the highest, 4.64 and 5.76% secreted in the extracellular part under growth conditions of 25°C and 16 h of incubation, respectively, after induction with IPTG (0.5 mM). Based on secretion analysis at different cellular locations, both recombinant proteins were highly secreted (p <0.05) in the periplasm rather than in the extracellular space. The purified periplasmic fraction recombinant protein has been confirmed to hydrolyze N-hexanoyl-L-Homoserine lactone (C6-HSL) AHLs. Enzyme activity aiiA-6xHis and N20-aiiA-6xHis against C6-HSL were 2.7x10-3 and 2.3x10-3 ?mol/minute/mg in 10 minutes of reaction, respectively. The percentages of C6-HSL substrate hydrolyzed by aiiA-6xHis and N20-aiiA-6xHis were 65.26 and 64.4%, respectively. This result is supported by the presence of the C6-HSL hydrolysis product (C6-HS), which is estimated to be present in the ion detection range (m/z) of 218.2. The conclusion of this study is that N-acyl homoserine lactonase from B. licheniformis DAHB1 can be expressed and secreted more in the periplasm than extracellularly in E. coli BL21 (DE3) using the recombinant plasmids pET-26b(+)-aiiA-6xHis and pET-26b( +)-N20-aiiA-6xHis.